Neutrophil-to-lymphocyte ratio as a predictive biomarker for hyperprogressive disease mediated by immune checkpoint inhibitors: a systematic review and meta-analysis - Pei, Bo; Zhang, Jue; Lai, Lin; Chen, Hui (Frontiers in Immunology, 2024)
Background: Hyperprogressive disease (HPD) is a novel pattern of paradoxically rapid tumor progression, which often leads to early death, mostly in the first two months of treatment with immune checkpoint inhibitors (ICIs). Currently, there is no validated biomarker to assess patients at risk of HPD.Aim: To systematically evaluate the predictive value of the neutrophil-to-lymphocyte ratio (NLR) in HPD and establish a reliable variable to support clinicians in defining personalized treatment strategies.Methods: PubMed, Embase, Web of Science, Scopus, and Cochrane Library databases were searched for studies published before December 31st, 2023.Newcastle-Ottawa scale (NOS) was used to evaluate the quality of eligible studies.The pooled odds ratios (ORs) and 95% confidence interval (CI) were calculated using random effects or fixed effects model to evaluate the association between NLR and the risk of HPD.Results: A total of 17 studies with 2964 patients were included for meta-analysis. The incidence of HPD across different types of tumors ranged from 6.3% to 35.6%. In the pooled analysis of the NLR and HPD, we identified NLR significantly associated with the risk of HPD (OR = 0.65; 95% CI: 0.46 to 0.91; p= 0.01) (I 2 = 52%, p = 0.007).In the future, NLR may serve as a remarkable biomarker for predicting the risk of HPD in clinical practice.